The interaction of interventricular pacing intervals and left ventricular lead position during temporary biventricular pacing evaluated by tissue Doppler imaging - Lane, R E (BMJ Group, 2007)
OBJECTIVE: To determine the effects of interventricular pacing interval and left ventricular (LV) pacing site on ventricular dyssynchrony and function at baseline and during biventricular pacing, using tissue Doppler imaging. METHODS: Using an angioplasty wire to pace the left ventricle, 20 patients with heart failure and left bundle branch block underwent temporary biventricular pacing from lateral (n = 20) and inferior (n = 10) LV sites at five interventricular pacing intervals: +80, +40, synchronous, −40, and −80 ms. RESULTS: LV ejection fraction (EF) increased (mean (SD) from 18 (8)% to 26 (10)% (p = 0.016) and global mechanical dyssynchrony decreased from 187 (91) ms to 97 (63) ms (p = 0.0004) with synchronous biventricular pacing compared to unpaced baseline. Sequential pacing with LV preactivation produced incremental improvements in EF and global mechanical dyssynchrony (p<0.0001 and p = 0.0026, respectively), primarily as a result of reductions in inter‐LV–RV dyssynchrony (p = 0.0001) rather than intra‐LV dyssynchrony (NS). Results of biventricular pacing from an inferior or lateral LV site were comparable (for example, synchronous biventricular pacing, global mechanical dyssynchrony: lateral LV site, 97 (63) ms; inferior LV site, 104 (41) ms (NS); EF: lateral LV site, 26 (10)%; inferior LV site, 27 (10)% (NS)). ECG morphology was identical during biventricular pacing through an angioplasty wire and a permanent lead. CONCLUSIONS: Sequential biventricular pacing with LV preactivation most often optimises LV synchrony and EF. An inferior LV site offers a good alternative to a lateral site. Pacing through an angioplasty wire may be useful in assessing the acute effects of pacing.